Additional evidence of the Holocene transgression in Lake Ladoga on the basis of an investigation of the beach deposits on the island of Mantsinsaari - I. Delusin; J. Donner (Bulletin of the Geological Society of Finland, 1995)
On the basis of a study of peats covered by a beach ridge on the island of Mantsinsaari in Lake Ladoga, the beginning of the Ladoga transgression here was dated at 2980 ± 80 radiocarbon years B.P. Similar dates have been obtained from the southern shores of the lake. They show that the transgression reached its maximum in the whole lake at the same time and that the River Neva was formed between about 2900 and 2500 B.P. There is no evidence in the sections studied on the island of Mantsinsaari of two stages in the Ladoga transgression during the Holocene. But the formation of the River Vuoksi dated at 5200 B.P. on the basis of ages from the bog Linnansuo in Imatra and the Lake Saimaa area probably accelerated the transgression.